PENGARUH PENGAPLIKASIAN FOUNDATION TERHADAP HASIL RIAS WAJAH CIKATRI - Harlini, Siti Miki; Hayatunnufus, Hayatunnufus; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The background of this research was there were many problems related to face skin surface that was not flat (cikatri face). The problems that emerged such as it was difficult to cover a hole by acne and it did not find the suitable technique thus a hole still appeared clearly. The purpose of this research was to analyze the application of cake foundation of makeup to cikatri. The type of this research was quasi experimental by non equivalent control group design. Object of this research was the woman that has a hole on face that was caused by acne at the age of 18-25 years old. The sample was taken by purposive sampling technique in volunteer sampling of the total 3 people. The results of this research proved that there was a significant influence from all treatment groups that were researched. Based on the result of t-test on experimental 1 (X1) t-count was 2.821 while t-table of provision t-table (0.25,6) = 2.477. Thus it was because t-count > t-table or significant scale 0.03 < 0.05. In experimental 2 t-count was 3.392 while t-table of provision t-table (0.25,6) = 2.477. Thus it was because t-count > t-table or significant scale 0.015 < 0.05. In experimental 3 t-count was 1.141 while t-table of provision t-table (0,25,6)= 2.477. Thus it was because t-count > t-table or significant scale 0.036 < 0.05. The result of t-test showed that group X1 has different significant with group X2 and X3, however group X2 and X3 did not show the significant different result. The good comparison result was in experimental treatment group 3 (X3). Thus, it can be recommended to use the repetition of the application of cake foundation on a hole that was caused by acne in makeup to cikatri face.Keywords: Aplication Foundation, Make up to Cikatri Face